Exchange and interest rate channels during a deflationary era: evidence from Japan, Hong Kong and China - Aaron Mehrotra (Bank of Finland, Institute for Economies in Transition (BOFIT), 2005)
We examine the role of the exchange and interest rate channels during recent deflation episodes in Japan, Hong Kong and China.We estimate open-economy structural vector autoregressive (SVAR) models for the three economies with different monetary regimes and varying degrees of openness.In both Japan and Hong Kong, shocks to the nominal effective exchange rate have a statistically significant impact on prices, with a notably stronger effect in Hong Kong.Our results provide evidence about the role of external influences in the deflation episodes of these economies, and could also be seen to weakly support suggestions to depreciate the currency in order to escape from a liquidity trap.The importance of the interest rate channel is also found to be high in Japan and Hong Kong.In China, where interest rates have not been an important monetary policy tool, neither exchange nor interest rate shocks significantly influence price developments.
URN:NBN:fi:bof-201408072029
Keywords: E31; F41; 330; Deflation; Zero lower bound; SVAR